The Impact of Television Migration on Indonesian Citizens - Adrian, Hadisti Nur (Politeknik Negeri Media Kreatif, 2023)
This research article aims to investigate the impact of television migration on Indonesian citizens. With the rising popularity of satellite television and over-the-top (OTT) streaming platforms, traditional terrestrial television has encountered significant challenges in retaining its viewership. This article explores the social and cultural consequences of television migration as well as the government interventions focusing on the potential effects it has on the Indonesian population. The results contribute to a deeper understanding of the implications of television migration in a rapidly evolving media environment.